Construct the truth table of (p \land \lnot q) \lor \lnot (q \land r) \lor (r \land p)
Use truth tables to prove that (p \land \lnot q) \lor \lnot (q \land r) \lor (r \land p) \iff p \lor \lnot q \lor \lnot r
p \land \lnot q) \lor \lnot (q \land r) \lor (r \land p)
= ((p ∧ ¬q) ∨ (¬(q ∧ r) ∨ (r ∧ p)))
Truth table:
Next, p \lor \lnot q \lor \lnot r
= (p ∨ (¬q ∨ ¬r))
Its truth table:
From both the tables, we can say that their output values are same.
Thus, (p \land \lnot q) \lor \lnot (q \land r) \lor (r \land p) \iff p \lor \lnot q \lor \lnot r
Comments
Leave a comment